2016
DOI: 10.1002/hec.3355
|View full text |Cite
|
Sign up to set email alerts
|

Myopic and Forward Looking Behavior in Branded Oral Anti‐Diabetic Medication Consumption: An Example from Medicare Part D

Abstract: We evaluate consumption responses to the non-linear Medicare Part D prescription drug benefit. We compare propensity-matched older patients with diabetes and Part D Standard or low-income-subsidy (LIS) coverage. We evaluate monthly adherence to branded oral anti-diabetics, with high end-of-year donut hole prices (>$200) for Standard patients and consistent, low (≤$6) prices for LIS. As an additional control, we examine adherence to generic anti-diabetics, with relatively low, consistent prices for Standard pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(34 reference statements)
2
0
0
Order By: Relevance
“…Ours is the first study to demonstrate how out-of-pocket payments for patients with diabetes influence the decision to reinitiate discontinued, branded antihyperglycemic medications at the beginning of the calendar year, thereby illustrating forward-looking behavior of patients within a narrow time span. This is in agreement with a previous study that observed reduced monthly medication adherence as the calendar year progressed in response to the donut hole in 2009 (26). It is also interesting to note that while no strong temporal patterns of reinitiation were observed for sulfonylureas, the HRs of reinitiation among nonsubsidized patients were still lower in the last few calendar months of the year.…”
Section: Discussionsupporting
confidence: 92%
“…Ours is the first study to demonstrate how out-of-pocket payments for patients with diabetes influence the decision to reinitiate discontinued, branded antihyperglycemic medications at the beginning of the calendar year, thereby illustrating forward-looking behavior of patients within a narrow time span. This is in agreement with a previous study that observed reduced monthly medication adherence as the calendar year progressed in response to the donut hole in 2009 (26). It is also interesting to note that while no strong temporal patterns of reinitiation were observed for sulfonylureas, the HRs of reinitiation among nonsubsidized patients were still lower in the last few calendar months of the year.…”
Section: Discussionsupporting
confidence: 92%
“…Drug purchases are initially constant and drop sharply once the coverage gap is reached, implying an estimated discount rate that is consistent with full myopia (i.e., equal to zero). A similar pattern of drug consumption under Medicare Part D may be found in Sacks et al (2017), Einav et al (2015), and Abaluck et al (2018). In the latter two studies, however, the estimated discount rates indicate some degree of forward-looking behaviour, which is considerably higher in Einav et al (2015).…”
Section: Related Literaturesupporting
confidence: 59%